COVID-19 and the upper and lower case revolts: Albert Camus, Giorgio Agamben and Slavoj Žižek read in parallax (Simbiótica. Revista Eletrônica, 2020)
This article proposes to articulate Literature and Philosophy so that we can indicate postures, which we will call revolts, that the pandemic crisis of the new coronavirus requires to be overcome. We understand that this discussion is useful to prevent us from being completely surprised at the possible confrontation of future catastrophes of this kind. Thus, we will appropriate Albert Camus' philosophical and literary work to distinguish two types of revolts that we initially identified in his fictional characters. Then, these characters serve as an illustration for the thoughts of two of the most prominent philosophers for their proposals and oppositions in the debate about the coronavirus: Giorgio Agamben and Slavoj Žižek.Keywords: Coronavirus; Camus; Agamben; Žižek.